The impact of women's television programs in combating violence against women - فەتحو, ئیبراهیم سەعید; قادر, ابتسام اسماعیل; Qadir, ژیا Abbas (Sulaimani Journal for Humanities, 2025)
This paper aims to understand about to what extent the Kurdish TV programs with specific focuses on feminine gender have influenced the women who work among female organizations and civil society organizations to counter the violence against women, as these women regarded to be elite among society and these programs could encourage them to be more active in their roles. To this end, a sample was chosen from women among organizations as an example to be asked some questions in a questionnaire form, after analysing their answers, this research concluded that the Kurdish TV programs have a medium effect on countering violence against women. This indicates that these programs were not design to make a huge influence on the cases of violence against women; therefore, this paper suggests that the quality of the female’s programs should be more developed especially in its content and forms in order to be newer and more attractive for women